Bovine Serum Albumin as a Versatile Platform for Cancer Imaging and Therapy - Wang, Jun; Zhang, Bingbo (Current Medicinal Chemistry, 2018)
Background: Due to the good biocompatibility, biodegradability, facile surface functionalization and high water solubility, Bovine serum albumin has gain increasing attention in the nanomedicine. Objective: Despite there are many reviews on albumin based nanoparticles, most of them focus on one aspect of the albumin functionality, e.g., drug delivery, cancer theranostics or half-life extension in vivo. This review aims to comprehensively summary bovine serum albumin as a versatile platform in the applications of cancer imaging and therapy. Methods: We review the extensive applications of bovine serum albumin in drug carrier, surface engineering and biomimetic synthesis for cancer imaging and therapy. Conclusion: Based on the studies reviewed, variety of in vitro and in vivo studies show good performance of bovine serum albumin as the drug carrier, surface modification agent and biomimetic template in cancer imaging and therapy. Nevertheless, there are still some issues to be solved, e.g., the technological parameters for enhancing the drug loading efficiency and controlling drug release, optimizing surface modification process to provide more stable nanoagents, investigation of the biomimetic mechanism, in-depth study of their toxicity, further exploring their bioapplications, etc.
Keywords: BSA